Law and Human Rights in Addressing Labor Problems during the Pandemic to Achieve Sustainable Development Goals - Arthanti, Berliana Dwi; Eka Pramudhita, Nabilla Dyah (Universitas Negeri Semarang, 2020)
The labor sector, as an important element in Indonesia's economic growth, has also felt the impact of Covid-19. Rampant unemployment, layoffs, not being registered with the BPJS, violation of workers/labor rights during this pandemic have given negative signals for national economic growth. This is because of the increase in the number of unemployed will increase the poverty rate, reducing the national Gross Domestic Product. The Act Number 13 of 2003 concerning Manpower, which is actually the main milestone in the enforcement of human rights and democracy for manpower, has not been implemented optimally. The domino effect of Covid-19, which not only lowers the economy, also affects the government's achievements in Sustainable Development Goals (SDGs). Therefore, It requires synergy from all fields and real human rights enforcement to ensure the workforce, revive the economy, and achieve the SDGs targets. This normative juridical research uses secondary data through literature study and qualitative analysis. Here, the researcher will understand the importance of human rights enforcement to deal with problems in the labor sector to achieve the government's targets in the SDGs program.